Human Dectin-1 deficiency impairs macrophage-mediated defense against phaeohyphomycosis - Rebecca A. Drummond; Jigar V. Desai; Amy P. Hsu; Vasileios Oikonomou; Donald C. Vinh; Joshua A. Acklin; Michael S. Abers; Magdalena A. Walkiewicz; Sarah L. Anzick; Muthulekha Swamydas; Simon Vautier; Mukil Natarajan; et al. (The Journal of Clinical Investigation, 2022)
Subcutaneous phaeohyphomycosis typically affects immunocompetent individuals following traumatic inoculation. Severe or disseminated infection can occur in CARD9 deficiency or after transplantation, but the mechanisms protecting against phaeohyphomycosis remain unclear. We evaluated a patient with progressive, refractory Corynespora cassiicola phaeohyphomycosis and found that he carried biallelic deleterious mutations in CLEC7A encoding the CARD9-coupled, β-glucan–binding receptor, Dectin-1. The patient’s PBMCs failed to produce TNF-α and IL-1β in response to β-glucan and/or C. cassiicola. To confirm the cellular and molecular requirements for immunity against C. cassiicola, we developed a mouse model of this infection. Mouse macrophages required Dectin-1 and CARD9 for IL-1β and TNF-α production, which enhanced fungal killing in an interdependent manner. Deficiency of either Dectin-1 or CARD9 was associated with more severe fungal disease, recapitulating the human observation. Because these data implicated impaired Dectin-1 responses in susceptibility to phaeohyphomycosis, we evaluated 17 additional unrelated patients with severe forms of the infection. We found that 12 out of 17 carried deleterious CLEC7A mutations associated with an altered Dectin-1 extracellular C-terminal domain and impaired Dectin-1–dependent cytokine production. Thus, we show that Dectin-1 and CARD9 promote protective TNF-α– and IL-1β–mediated macrophage defense against C. cassiicola. More broadly, we demonstrate that human Dectin-1 deficiency may contribute to susceptibility to severe phaeohyphomycosis by certain dematiaceous fungi.